Different Types of ANCA Determine Different Clinical Phenotypes and Outcome in ANCA-Associated Vasculitis (AAV) - Bantis, Kostas; Stangou, Maria J.; Kalpakidis, Savvas; Nikolaidou, Christina; Lioulios, George; Mitsoglou, Zoi; Iatridi, Fotini; Fylaktou, Asimina; Papagianni, Aikaterini (Frontiers in Medicine, 2022)
Aim: Accumulating evidence supports the use of ANCA type to classify different clinical entities. We aimed to evaluate whether the presence and type of-ANCA determine different diseases, based on clinical phenotypes, renal involvement and response to treatment. Methods: Differences in terms of clinical manifestations, disease activity, laboratory parameters and histology were recorded between patients with focal necrotizing glomerulonephritis (FNGN) due to MPO-, PR3-ANCA(+) and ANCA(-) disease at time of diagnosis. Patients were treated with the same protocol, and followed up for 24months, in a scheduled basis of every month for the first, and every 3 months for the second year. Primary end points were i) Combined end stage renal disease (ESRD) and/or death and ii) The presence of major or minor relapse during follow-up, and secondary end point was the combination of ESRD and reduction of eGFR ≥50%. Results: Ninety two patients (M/F 39/53, mean age 59.1±15years) diagnosed with FNGN due to AAV, 36(39.1%) PR3-ANCA, 39(42.4%) with MPO-ANCA and 17(18.5%) ANCA(-) were included. Number of involved systems differed significantly between PR3-, MPO-ANCA and ANCA(-), with only renal involvement in 3%, 25.5% and 29% of patients, 2 systems involved in 33%, 31% , 59%, and >3 systems in 64%, 43.5% and 12%, respectively, p=0.002. Histology classification revealed focal, crescentic, mixed and sclerotic type in 14%, 64%, 19%, 3% of PR3-ANCA(+), 8%, 28%, 18%, 46% of MPO-ANCA and 41%, 29%, 6% and 24% of ANCA(-), respectively, p<0.0001. Primary end point of ESRD±Death was reached in 11(30.6%), 16(41%) and 6(35.5%) of patients with PR3 ANCA(+), MPO ANCA(+) and ANCA (-), respectively, p=NS, similarly, ESRD± >50% e-GFR reduction in 8(22.2%), 15(38.5%) and 5(29.4%) patients, respectively, p=NS, meaning that MPO-ANCA(+) patients showed a propensity to decline renal function. Rate of relapse was increased in the presence of PR3-ANCA(+), 14(38.9%), 4(11.8%) and 2(10.3%) of PR3-ANCA(+), MPO-ANCA(+) and ANCA(-) patients, had at least one relapse during the two year follow up p=0.006. Conclusion: Clinical phenotype and renal histology differ significantly between PR3-ANCA(+), MPO-ANCA(+) and ANCA(-) disease and FNGN, however, renal function outcome is similar, despite the increased rate of relapses in PR3-ANCA(+) patients.